92. Patient's Peak Skin Dose evaluation using GafChromic films in interventional cardiology procedures and its correlation with other dose indicators. (December 2018) - Valero, C.; Cutaia, C.; Poli, M.; Peroni, G.; Pasquino, M.; Stasi, M.
Abstract : Purpose: Interventional Cardiology (IC) procedures have increased in number and complexity during last years and the concern about radiation dose to patients is increasing as well. The aim of the work is to investigate the radiation exposure of patients undergoing IC procedures and to support follow-up strategies for patients at risk for deterministic effects. Methods: PSD was measured in vivo using radiochromic GafChromic XR-RV3 films during Coronary Angiography (CA) and Angioplasty (PTCA) performed at our institution by means of an Allura Clarity and Axiom Artis angiographic system. Dose Area Product, Cumulative Dose at the Interventional Reference Point and Fluoroscopy Time of these procedures were collected from the Radiation Dose Structured Reports. Linear regression between measured PSD and dosimetric parameters was investigated. Results: Data were analysed from 42 procedures. The dosimetric indicators values are generally higher for PTCA than for CA, due to the different procedure complexity while, for the same type of procedure, values result higher on Axiom. The best correlation between PSD and dosimetric indicators was obtained with CD values (R2 about 0.8). The correlations are shown in Figure I for both the angiographic systems. The threshold CD values corresponding to a PSD of 2 Gy (threshold for deterministic skin effects) are 6.0 Gy for Axiom and 3.5 Gy for Allura system, respectively. Conclusions: IC procedures can deliver high levels of radiation dose to patients. The study confirmed that dose increases with the complexity of procedures and can significantly depend on the X-Rays system. The method used to correlate PSD and CD can be easily and effectively implemented and can support clinicians in identifying and managing patients at risk for deterministic effects.